2022
DOI: 10.2196/34554
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Support for Decision-Making in Kidney Transplantation: Step-by-step Development of a Technological Solution

Abstract: Background Kidney transplantation is the preferred treatment option for patients with end-stage renal disease. To maximize patient and graft survival, the allocation of donor organs to potential recipients requires careful consideration. Objective This study aimed to develop an innovative technological solution to enable better prediction of kidney transplant survival for each potential donor-recipient pair. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The popularity of these methods could be explained by the fact that they are generally associated with a greater potential for explainability of the results, which facilitates their translation into clinical practice. Other methods, such as support vector machine and recurrent neural networks, have also gained popularity in recent years, as they are known to show better performance for certain tasks ( Paquette et al, 2021 ). Traditional statistical methods are also widely used.…”
Section: Discussionmentioning
confidence: 99%
“…The popularity of these methods could be explained by the fact that they are generally associated with a greater potential for explainability of the results, which facilitates their translation into clinical practice. Other methods, such as support vector machine and recurrent neural networks, have also gained popularity in recent years, as they are known to show better performance for certain tasks ( Paquette et al, 2021 ). Traditional statistical methods are also widely used.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating these models indicated that neural network-based models, particularly the RNN, exhibited superior discriminative abilities (with scores of 0.65, 0.66, and 0.66, respectively) compared to the Cox model and random survival forest model (with scores of 0.65 and 0.64, respectively). The RNN model thus strikes a balance between accurate predictions and practical applicability for healthcare professionals [66].…”
Section: Donor-recipient Matching and Organ Allocation Strategiesmentioning
confidence: 99%
“…A summary of these studies is shown in Table 3. Furthermore, several review papers discussing AI in kidney transplantation and the assessment of renal transplant prognosis using classical machine learning approaches are available for interested readers in the additional resources [27,[40][41][42][43][44][45]. Sensitivity of 90-93% for intra-institutional and 77% for inter-institutional dataset…”
Section: Ai Advances In Transplant Kidney Pathologymentioning
confidence: 99%